2021
DOI: 10.1038/s41370-021-00323-7
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between air pollutants and maternal socioeconomic factors on preterm birth in California urban counties

Abstract: Background Preterm birth is the leading cause of perinatal morbidity and mortality in the U.S. and disparities among racial and ethnic groups persist. While etiologies of preterm birth have not been fully elucidated, it is probable that environmental and social factors play a role. Objective We hypothesized that there is an interactive association between exposure to fine particulate matter (PM2.5) or ozone (O3) and neighborhood socioeconomic factors that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…The past decade has witnessed mounting attention on researching the association between maternal exposure to air pollutants and adverse birth outcomes. Many studies have demonstrated positive associations between ambient air pollution exposure and PTB [ 23 , 24 , 25 , 26 ], especially for PM 2.5 and PM 10 . Lei Yuan and Ying Tian (2019) reviewed 42 studies on the association between maternal exposure to PM 2.5 and PTB; among 18 studies selected, prenatal PM 2.5 exposure has strong effects on PTB [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The past decade has witnessed mounting attention on researching the association between maternal exposure to air pollutants and adverse birth outcomes. Many studies have demonstrated positive associations between ambient air pollution exposure and PTB [ 23 , 24 , 25 , 26 ], especially for PM 2.5 and PM 10 . Lei Yuan and Ying Tian (2019) reviewed 42 studies on the association between maternal exposure to PM 2.5 and PTB; among 18 studies selected, prenatal PM 2.5 exposure has strong effects on PTB [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Predominantly Black neighborhoods are also characterized as having higher allergen counts as well as pollution levels of almost 1.54 times higher than the overall population [ 73 ]. Multiple studies have indicated that pollution can increase the risk of preterm births and lead to the development of unfavorable health conditions such as diabetes [ 74 , 75 ]. The susceptibility of Black mothers to having preterm births is likely contributed to by their tendency to reside in relatively unfavorable environments.…”
Section: Neighborhood and Built Environmentmentioning
confidence: 99%
“…Examining these combined exposures is important for understanding how total neighborhood contexts can impact early life outcomes. Studies on the potential for neighborhood-level socioeconomic status to modify the relationship between air pollutants and birth outcomes suggest the interactions between neighborhood factors may be synergistic (Généreux et al, 2008;Mekonnen et al, 2021;Padula et al, 2014;Ponce et al, 2005;Yi et al, 2010). These studies investigated relationships between SES and single environmental exposures.…”
Section: Introductionmentioning
confidence: 99%
“…These studies investigated relationships between SES and single environmental exposures. For example, Généreux et al, 2008 included distance to roadways as the exposure of interest, Padula et al (2014) included ambient carbon monoxide, nitrogen dioxide, and particulate matter, and Mekonnen et al (2021) included particulate matter and ozone. A review of interactions between social determinants and environmental exposures on perinatal and childhood health outcomes found that 28 of the 39 (72%) review studies reported synergistic associations between social and environmental factors (Appleton et al, 2016).…”
Section: Introductionmentioning
confidence: 99%